Evaluation of the relationship of low affinity receptor gene polymorphism to IGE — FCƐRII (RS 28364072 (T2206C)) with clinical and anamnestic data of bronchial asthma in children - R. R. Gafurova; R. M. Fayzullina; Z. A. Shangareeva; K. V. Danilko (Аллергология и Иммунология в Педиатрии, 2023)
.